2016
DOI: 10.1167/tvst.5.6.6
|View full text |Cite
|
Sign up to set email alerts
|

Reference Clinical Database for Fixation Stability Metrics in Normal Subjects Measured with the MAIA Microperimeter

Abstract: PurposeThe purpose of this study was to establish a normal reference database for fixation stability measured with the bivariate contour ellipse area (BCEA) in the Macular Integrity Assessment (MAIA) microperimeter.MethodsSubjects were 358 healthy volunteers who had the MAIA examination. Fixation stability was assessed using two BCEA fixation indices (63% and 95% proportional values) and the percentage of fixation points within 1° and 2° from the fovea (P1 and P2). Statistical analysis was performed with linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 24 publications
4
31
1
Order By: Relevance
“…Rohrschneider et al [3], Weingessel et al [4], and Morales et al [21,22] found a decrease in fixation stability with an increasing age in normal subjects, and older observers showed greater variability in their fixations. Age might be a significant factor for fixation loss, but microperimetry is a psychophysical test; thus, it might present a learning effect for fixation stability.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Rohrschneider et al [3], Weingessel et al [4], and Morales et al [21,22] found a decrease in fixation stability with an increasing age in normal subjects, and older observers showed greater variability in their fixations. Age might be a significant factor for fixation loss, but microperimetry is a psychophysical test; thus, it might present a learning effect for fixation stability.…”
Section: Discussionmentioning
confidence: 96%
“…With microperimetry biofeedback training, patients with macular diseases who have lost foveal fixation capabilities are trained to relocate their preferred retinal locus (PRL) into an area with better sensitivity. This training to relocate the PRL can improve the fixation behavior and, thereby, visual performance [21][22][23]24,25]. Several authors have demonstrated that this training is effective in patients with loss of central vision secondary to macular pathologies, particularly in cases with geographic atrophy secondary to AMD [21,23,24,26]; however, it has also been reported that patients with macular disease may use two or more PRLs for fixation [24,25,27].…”
Section: Discussionmentioning
confidence: 99%
“…There are several commercially available microperimetry devices, all with defining features that potentially drive one to be the instrument of choice over others. The key differences are range of stimulus intensity (0e20 dB to 0e50 dB), eye-tracker frequency (8e30 Hz), 28 background illumination (1.27 cd/m 2 e10 cd/m 2 ), and imaging features (color fundus photography, scanning laser ophthalmoscope, OCT) (Table). 15,26 Different features may be better suited to answering different questions; for example, imaging frequency, which is not necessarily the rate-defining step for technical stimulus placement or adjustment, may not be as important for consideration as dynamic range of the stimulus intensity.…”
mentioning
confidence: 99%
“…Most studies of the MAIA have used one of two available test methods: a 68‐point test that is similar to the 10–2 programme of the Humphrey Field Analyser, or the so‐called Standard test that examines 37 points within the central 10 degrees. The 37‐point test takes about 6 min per eye …”
mentioning
confidence: 99%
“…The Nidek MP3 also does this. The MAIA additionally reports the area of the ellipse enclosing the fixational jitter and rates the fixation error as: ‘stable, relatively unstable, or unstable’ …”
mentioning
confidence: 99%